Hibernation is a must-have feature in a laptop. I can work on my programming, then hibernate the machine in 30 seconds, take a nap and resume the machine to the state before it hibernates in 30 seconds and continue my work — I can just continue my work from I stop seamlessly. However, the hibernation function seems to be missing in Linux Mint Maya (KDE) in my Dell Vostro 3450. The followings are the patches to overcome this issue.
The patches include:
1. Prepare the scripts to hibernate.
2. Make an hibernation icon in the start menu.
3. Solve the noisy fan issue (due to the hybrid card) after resume from hibernation.
After watching the movie “The Internship” starred by Vince Vaughn and Owen Wilson, I decided to submit my PhD internship application to Google. An influential movie, I guess. 🙂
Of cause, it is a one in a million chance. At least, I try.
I own a very old fashion scientific calculator and it can’t solve any simultaneous equations like those new calculators (not even 2×2!). The situation goes worst when I try to do my Circuit Theory tutorial, in which I need to solve many simultaneous equations. Can’t I just concentrate on forming the equations and let someone to solve them for me?
Well! Let the Python do it!
All you have to do is forming the proper equations. Then, fire up the following script. Key in the proper coefficients of each equation when Python asks.
Please feel free to copy and use it anywhere you like.
#!/bin/python import numpy as np print 'How many variables ?' print '>> ', total_variable = int(raw_input()) # User key in all the variable numbers equation_list =  for i in range(total_variable): print print 'Please enter the coefficients of the #%d equation.' % (i+1) print 'For example: (1)*x0 + (2)*x1 = (3) ---> "1 2 3"' print '>> ', user_input = raw_input() user_token_str = user_input.split() assert (len(user_token_str)== (total_variable +1)) user_token = [float(u) for u in user_token_str] equation_list.append(user_token) print equation_arr = np.array(equation_list) # # A * X = Y # Given A and Y, we need to find X. # Y_arr = equation_arr[:, -1:] A_arr = equation_arr[:, :-1] print 'Y_arr:' , Y_arr print 'A_arr:' , A_arr X_arr = np.linalg.solve(A_arr, Y_arr) print 'Answer:' for i, x in enumerate (X_arr): print 'x%d value: %f' % (i, x)
Paper accepted in IEICE.
This gallery contains 1 photo.
I went to a grant proposal defence few days ago. They only asked me two questions. 1. Is your work pattern-able? 2. Is your work commercialize-able. They want money-outcome now.
Someone sent me this question:
“Solve for the currents in the circult of Figure 2, if E(t)=5H(t-2) and the initial currents are zero. [Hint : Use Lapalce transform to solve this problem.]”
So, to solve it, form mesh analysis of two loops. Then, convert them from time domain to complex domain with Laplace transform. Next, solve I1 and I2 with normal algebra. Then only inverse I1 and I2 back to time domain.
Of cause, if you familiar with Sage, you can solve it within 30min (or lesser?).
t = var('t') s = var('s') I1 = var('I1') I2 = var('I2') E(t) = 5*unit_step(t-2) E(s) = E(t).laplace(t, s); E(s) # >> 5*e^(-2*s)/s equation = [ -E(s) + I1*20*s + 10*(I1-I2) == 0, 10*(I2-I1) + I2*30*s + I2*10 == 0 ] solution = solve(equation, I1, I2); solution # >> [[I1 == 1/2*(3*s + 2)*e^(-2*s)/(6*s^3 + 7*s^2 + s), I2 == 1/2*e^(-2*s)/(6*s^3 + 7*s^2 + s)]] # Note that Sage cannot inverse-Laplace time-delay function. So, taking out e^(-2*s) I1(s) = 1/2*(3*s + 2)/(6*s^3 + 7*s^2 + s) I2(s) = 1/2/(6*s^3 + 7*s^2 + s) i1_temp(t) = I1(s).inverse_laplace(s, t); i1_temp # >>t |--> -1/10*e^(-t) - 9/10*e^(-1/6*t) + 1 i2_temp(t) = I2(s).inverse_laplace(s, t); i2_temp # >> t |--> 1/10*e^(-t) - 3/5*e^(-1/6*t) + 1/2 # Referring to Table. For G(s)= e^(as)F(s), the inverse is g(t) = f(t-a). u(t) = unit_step(t) i1(t) = u(t-2) * ( -1/10*e^(-(t-2)) - 9/10*e^(-1/6*(t-2)) + 1 ) # Answer for i1 i2(t) = u(t-2) * ( 1/10*e^(-(t-2)) - 3/5*e^(-1/6*(t-2)) + 1/2 ) # Answer for i2 p1 = plot(i1(t), 0, 10, color='blue', legend_label='i1(t)') p2 = plot(i2(t), 0, 10, color='red', legend_label='i2(t)') show(p1 + p2)
And, the final answers are: